Flipped Learning for Math Instruction - Bergmann, Jonathan; Sams, Aaron (Book collections on Project MUSE., 2015)
In this book, the authors discuss how educators can successfully apply the flipped classroom model to teaching math. Each chapter offers practical guidance, including how to approach lesson planning, what to do with class time and how the flipped model can work alongside learning through inquiry.